José Sebastián Barranca: filólogo y lingüista - Solís Fonseca, Gustavo (2007)
The article describes the philologist and linguist facet of the naturalist José Sebastián Barranca. It highlights his production in Andean and Amazonian Amerindian languages, pointing out his most relevant works.